Clinically isolated syndromes - Miller, David H; Chard, Declan T; Ciccarelli, Olga (Lancet neurology, 2012)
Clinically isolated syndrome (CIS) is a term that describes a first clinical episode with features suggestive of multiple sclerosis (MS). It usually occurs in young adults and affects optic nerves, the brainstem, or the spinal cord. Although patients usually recover from their presenting episode, CIS is often the first manifestation of MS. The most notable risk factors for MS are clinically silent MRI lesions and CSF oligoclonal bands; weak or uncertain risk factors include vitamin D deficiency, Epstein-Barr virus infection, smoking, HLA genes, and miscellaneous immunological abnormalities. Diagnostic investigations including MRI aim to exclude alternative causes and to define the risk for MS. MRI findings incorporated into diagnostic criteria in the past decade enable MS to be diagnosed at or soon after CIS presentation. The course of MS after CIS is variable: after 15–20 years, a third of patients have a benign course with minimal or no disability and a half will have developed secondary progressive MS with increasing disability. Prediction of the long-term course at disease onset is unreliable. Disease-modifying treatments delay the development from CIS to MS. Their use in CIS is limited by uncertain long-term clinical prognosis and treatment benefits and adverse effects, although they have the potential to prevent or delay future tissue damage, including demyelination and axonal loss. Targets for future therapeutic progress are to achieve safe and effective long-term immunomodulation with neuroprotection and repair.